2018
DOI: 10.20448/journal.501.2018.51.19.28
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy Rule and its Performance under Inflation Targeting in Thailand

Abstract: This article reviews the Thailand monetary policy rule and its performance under the adoption of inflation targeting regime since 2000. The study estimates the policy reaction function to see if the inflation targeting has been linked with an inflation-responsive monetary policy rule, and investigates whether the monetary policy rule would actually have its transmission effect on inflation, through tracing the impulse responses of inflation rate to monetary policy shocks. The main findings are as follows. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…They reported that Thailand's monetary policy rule, under inflation targeting, is characterized by a forward‐looking inflation‐exchange rate responsive rule, which is countercyclical to inflation in the long run. Consistent with Mugume (), Taguchi and Wanaslip () conclude that monetary policy in Thailand, under inflation targeting, has only a marginal transmission effect on inflation, perhaps due to the slow adjustment of policy rate. Estimated the policy reaction function of Thailand to see if the inflation targeting regime was linked to the inflation‐responsive monetary policy rule and investigated whether the monetary policy rule has a transmission effect on inflation.…”
Section: Review Of Empirical Studiesmentioning
confidence: 55%
See 2 more Smart Citations
“…They reported that Thailand's monetary policy rule, under inflation targeting, is characterized by a forward‐looking inflation‐exchange rate responsive rule, which is countercyclical to inflation in the long run. Consistent with Mugume (), Taguchi and Wanaslip () conclude that monetary policy in Thailand, under inflation targeting, has only a marginal transmission effect on inflation, perhaps due to the slow adjustment of policy rate. Estimated the policy reaction function of Thailand to see if the inflation targeting regime was linked to the inflation‐responsive monetary policy rule and investigated whether the monetary policy rule has a transmission effect on inflation.…”
Section: Review Of Empirical Studiesmentioning
confidence: 55%
“…They reported that Thailand's monetary policy rule, under inflation targeting, is characterized by a forward‐looking inflation‐exchange rate responsive rule, which is countercyclical to inflation in the long run. Consistent with Mugume (), Taguchi and Wanaslip () conclude that monetary policy in Thailand, under inflation targeting, has only a marginal transmission effect on inflation, perhaps due to the slow adjustment of policy rate.…”
Section: Review Of Empirical Studiesmentioning
confidence: 55%
See 1 more Smart Citation
“…In recent investigations, researchers have come up with better ways of dealing with these three puzzles and most of which is fashioned after the framework set by Lucas (1972) where rational expectation approach to the monetary policy study was recommended. Recent studies that have adopted the same approach include (Cochrane, 1998;Kahn et al, 2002;Zhang, 2009;Hsing, 2014;Aguir et al, 2015;Edeme and Obiayo, 2017;Adjei, 2018;Taguchi and Wanasilp, 2018) to mention but a few.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the Philippines's policy rule, Salas (2006) revealed that the policy rate reacted to inflation effectively enough to stabilize inflation in a forward-looking manner after the IT adoption. As for Thailand's policy rule, Lueangwilai (2012) verified the contemporaneous rule of the policy rate responding to inflation and exchange rate movement; and McCauley (2006) and Taguchi and Wanasilp (2018) identified the inflation-responsive rule with forward-looking manner. Vietnam's monetary policy rule has not examined specifically by a policy reaction function, although the monetary policy was studied from the administration perspective (e.g., To et al, 2012) and from the transmission mechanism (e.g., Bui and Tran, 2015).…”
Section: Literature Review and This Study's Contributionsmentioning
confidence: 94%